A systematic review on the correlation between COVID-19 and lower urinary tract symptoms - Ashkan Shafigh; Amir Mohammadi-Garebagh; Kavous Shahsavarinia; Sona Tayebi; Ali Mostafaei; Hanieh Salehi-Pourmehr; Sakineh Hajebrahimi (Journal of Clinical Virology Plus)
COVID-19 can lead to extrapulmonary symptoms such as Lower Urinary Tract Symptoms (LUTS). We aimed to investigate the impact of the severity of SARS-CoV-2 infection on the lower urinary tract in patients affected by COVID-19. We conducted a comprehensive literature search using the terms ''COVID-19,'' ''SARS-CoV-2,'' and ''Lower Urinary Tract Symptoms'' with various combinations in MEDLINE, Scopus, ProQuest, Web of Science, Google Scholar, and Cochrane Library, including Cochrane Central Register of Controlled Trials (CENTRAL) and Cochrane Database of Systematic Reviews (CDSR) databases. The studies were selected based on eligibility criteria, and quantitative data were extracted using the data extraction tool from JBI-MAStARI. A total of 988 articles were found through the literature search. Twenty-five articles were included in our qualitative evaluation, and seven studies were included in the quantitative analysis. The qualitative publications were systematically reviewed separately under the titles of LUTS, benign prostatic hyperplasia (BPH), and kidney failures or kidney transplant recipients. The analysis of eligible studies showed a 3.3 % prevalence of LUTS in infected patients (95 % CI: 2.0 % - 5.3 %; Q-value: 1021.397, I2: 97.45 %). Furthermore, frequency and urgency were the most prevalent symptoms in the eligible meta-analysis studies, with 15.3 % (95 % CI: 5.7 % – 34.9 % in 4 studies) and 11.5 % (95 % CI: 7.1 % - 18.1 % in two studies), respectively. The prevalence of LUTS among COVID-19 patients was 3.3 %, with common symptoms including urinary frequency, urgency, UTI, and hematuria. Long-term follow-up and consideration of pre-existing LUTS are essential for improving understanding and clinical management.